The Discretion of Internal Prosecutor Apply in Article 2 & 3 for Law Eradication of Corruption - Kirana, Imme; Khairani, Khairani; Mulyati, Nani (Universitas Islam Sultan Agung, 2024)
The criminal act of corruption is the favorite as if it never gets old, precisely the term extraordinary crime corruption, in addition, the perpetrators of criminal acts of corruption are mostly legal subjects who play a role based on the authority they have. However, it is not uncommon for prosecutors to use the type of subsidiary charge in prosecuting them to determine Article 2 as the primary charge and Article 3 as a subsidiary charge, even though it is clear that the perpetrator has abused their authority and resulted in financial losses to the State. This is a concern for the author to research facultatively on charges of subsidiarity for violations of Article 2 and 3. In this research, the author uses a type of Normative Juridical research, namely legal research that is oriented to secondary data and refers to legal material sources such as Law Number 20 of 2001 Concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes. The results of the research explained that the type of subsidiary indictment by making Article 2 the primary indictment and Article 3 the subsidiary indictment is a form of prosecutorial discretion in eradicating criminal acts of corruption effectively and efficiently so that it is unlikely that the defendant will escape criminal responsibility. Furthermore, Article 3 is the systematic lex specialist of Article 2 of the Corruption Eradication Law, because in criminal acts of corruption, the element